2005
DOI: 10.1038/emm.2005.64
|View full text |Cite
|
Sign up to set email alerts
|

Effective glycemic control achieved by transplanting non-viral cationic liposome-mediated VEGF-transfected islets in streptozotocin-induced diabetic mice

Abstract: Hypoxic damage is one of the major causes of islet graft failure and VEGF is known to play a crucial role in revascularization. To address the effectiveness of a cationic lipid reagent as a VEGF gene carrier, and the beneficial effect of VEGF-transfected islets on glycemic control, we used effectene lipid reagent in a transfection experiment using mouse islets. Transfection efficiencies were highest for 4 µg/µL cDNA and 25 µL effectene and cell viabilities were also satisfactory under this condition, and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…We also observed that commercially available liposome, Lipopectin, was not effective in gene expression in agreement with a previous report (Byk et al, 1998). Intratumoral injection of a complex of adenovirus and liposome led to enhanced adenoviral transduction compared to injecting just the adenovirus alone (Lee et al, 2000;Chae et al, 2005). Lipofectamin-mediated gene transfer was noted to be ineffective in liver-directed gene transfer in non-human primates (Sullivan et al, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…We also observed that commercially available liposome, Lipopectin, was not effective in gene expression in agreement with a previous report (Byk et al, 1998). Intratumoral injection of a complex of adenovirus and liposome led to enhanced adenoviral transduction compared to injecting just the adenovirus alone (Lee et al, 2000;Chae et al, 2005). Lipofectamin-mediated gene transfer was noted to be ineffective in liver-directed gene transfer in non-human primates (Sullivan et al, 1997).…”
Section: Discussionsupporting
confidence: 79%
“…Normalized blood glucose levels in the long termKawakami et al (2001)[86] Cationic lipid reagentVEGFDirect transplantationLeft kidney capsuleNormalized blood glucose level. Preserved transplanted islet cells with increasing vascularizationChae et al (2005)[43] R3V6 peptide micellessiRNA-iNOS, 17b-estradiolDirect transplantationLeft kidney capsuleImproved glycemic control. Reduced apoptosis of transplanted islet cellsHwang et al (2015)[87] Magnetic iron oxide nanoparticlessiRNA-human caspase-3Direct transplantationLeft kidney capsuleDecreased apoptosis in transplanted islet cellsWang et al (2011)[88] Magnetic iron oxide nanoparticlessiRNA-β 2 microglobulinDirect transplantationLeft kidney capsuleDelayed onset of diabetes mellitus caused by immune rejectionWang et al (2012)[89]

Abbreviations : GLP-1: glucagon-like peptide-1; IBMIR: instant blood-mediated inflammatory reactions; PEG: polyethylene glycol; PGA: polyglycolic acid; PET: polyethylene terephthalate; bFGF: basic fibroblast growth factor; CR1: soluble complement receptor 1; PVA: polyvinyl alcohol hydrogel; VEGF: vascular endothelial growth factor; R3V6: three arginine and six valine; siRNA: short interfering RNA; iNOS: inducible nitric oxide synthase.

…”
Section: Islet Cell Transplantationmentioning
confidence: 99%
“…Islet cells over-expressing GLP-1 or vascular endothelial growth factor were shown to preserve mass and function better compared with control islet cells when transplanted into the kidney capsule of a mouse model of diabetes mellitus [43,54]. Another study reported that inducible nitric oxide synthase-siRNA and 17b-estradiol-siRNA using the R3V6 peptide vector, which comprises three arginine and six valine and which forms self-assembled micelles in aqueous solution, transplanted into islet cells and delivered into the renal subcapsular space of a mouse model of diabetes mellitus suppressed cytokine-induced transplanted islet cell destruction, resulting in better control of blood glucose levels [87].…”
Section: Islet Cell Transplantationmentioning
confidence: 99%
“…A number of studies have investigated VEGF in islet transplantation, either delivered as a protein or via gene therapy [135,136]. Olsson and colleagues [137] found that while the culture of islets with VEGF improved graft revascularization one month post-transplantation, VEGF treated islets had similar or worse vascular engraftment compared to control islets.…”
Section: Vascular Endothelial Growth Factormentioning
confidence: 99%